2004
DOI: 10.1093/geront/44.5.633
|View full text |Cite
|
Sign up to set email alerts
|

Work Stressors and the Quality of Life in Long-Term Care Units

Abstract: Long-term care units are encouraged to review their practices so that employee well-being is supported. Attention also should be focused on unit size, as small units appear better able to help employees cope with work stress, resulting in better quality of life for residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 40 publications
3
46
0
1
Order By: Relevance
“…Annerstedt [28] found that staff in small group-living units reported greater competence, more knowledge in dealing with dementia, and greater satisfaction than those in traditional nursing homes. Pekkarinen [29] reported that large units increased time pressure on employees and reduced quality of life of residents. Demands on staff were lower and social support from co-workers was higher in small group-living homes than in larger traditional nursing homes [30]; satisfaction was also higher and burnout lower in these small homes.…”
Section: Discussionmentioning
confidence: 99%
“…Annerstedt [28] found that staff in small group-living units reported greater competence, more knowledge in dealing with dementia, and greater satisfaction than those in traditional nursing homes. Pekkarinen [29] reported that large units increased time pressure on employees and reduced quality of life of residents. Demands on staff were lower and social support from co-workers was higher in small group-living homes than in larger traditional nursing homes [30]; satisfaction was also higher and burnout lower in these small homes.…”
Section: Discussionmentioning
confidence: 99%
“…Pekkarinen and colleagues, in Finland, took a different approach in looking at the effects of unit size [35]. They argue that many resident quality of life domains stem from the interpersonal activities between staff and residents as they receive care.…”
Section: Household or Group Sizementioning
confidence: 99%
“…Some dissatisfied staff show greater aggression towards other workers [7] and residents [8]. Job dissatisfaction is associated with reduced quality of resident care [9] and resident quality of life [10], as well as reduced ability of organizations to change [11]. Conversely, caregivers (including care aides) who report perceiving high quality of care in their facilities also report higher satisfaction with their job [12].…”
Section: Introductionmentioning
confidence: 99%